Urban heat and within-city residential sorting - BORSKY, Stefan (Institutional Knowledge at Singapore Management University, 2024)
This study presents new causal evidence on how urban heat contributes to sorting within a city. We estimate a discrete choice residential sorting model that includes census-tract fixed effects and controls for open space and green coverage to analyze how differences in urban heat at the census-tract level influence the location choices of New York City homeowners given their race, ethnicity, and income. Our results show clear patterns of residential sorting, with whites and high-income households outcompeting other racial/ethnic groups and low-income households for housing in cooler neighborhoods. Our counterfactual exercise, inspired by Cool Neighborhoods NYC, reveals that heat-mitigation policies can make poorer and minority households, on average, worse off. These findings are striking, considering that such programs often aim to enhance welfare in heat-exposed neighborhoods predominantly inhabited by low-income and minority households.